Ultrahigh-capacity dynamic holographic displays via anisotropic nanoholes. Issue 4 (11th January 2017) - Zhang, Xiaohu; Jin, Jinjin; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Gao, Ping; Zhao, Zeyu; Wang, Yanqin; Wang, Changtao; Luo, Xiangang
Abstract : The information hidden in the evanescent waves can be used for holographic images in the Fraunhofer region via off-axis illumination. Abstract : For the miniaturization of optical holographic and data recording devices, large information capacity or data density is indispensable but difficult to obtain using traditional technologies. In this paper, an ultrahigh-capacity metasurface hologram is proposed by encoding information in deep-subwavelength scale nanohole arrays, which can be reconstructed via a light beam with proper designed incident angles. The imaging information capacity of the two-dimensional (2D) hologram, defined by the distortion-free region, can be increased 11.5 times, which is experimentally demonstrated by focused ion beam (FIB) milling of an ultrathin metallic film. We also prove the feasibility of a three-dimensional (3D) hologram of spiral lines designed by using the point source algorithm. Benefitting from the ultrahigh capacity of the deep-subwavelength metasurface, dynamic holographic displays can be realized by controlling the incident angle. The method proposed here can also be leveraged to achieve large capacity optical storage, colorful holographic displays, lithography technology etc .